2022
DOI: 10.1007/s11109-022-09842-x
|View full text |Cite
|
Sign up to set email alerts
|

The Unequal Effects of the COVID-19 Pandemic on Political Interest Representation

Abstract: The COVID-19 pandemic is viewed by many as the biggest global crisis since WWII and had profound effects on the daily lives of people and decision-making worldwide. Using the pandemic as a system-wide agenda shock, we employ a difference-in-differences design to estimate its causal effects on inequalities in political access, and social media prominence among business interests and NGOs. Our argument is twofold. First, the urgency and uncertainty of crises incentivized decision-makers to privilege providing ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Countries with wealthier and more organised elites were, on average, slower in imposing lockdown measures. This resonates with recent studies focusing on policymaking during the pandemic in Europe, which has shown that pandemic politics became the focus of intense lobbying competition, in which business groups tended to predominate (Eady and Rasmussen, 2022). As Crepaz et al, (2022) argue, because the pandemic would cause important economic disruptions, governments had reason to prioritise the mitigation of financial distress on economic groups, particularly of those with the resources to put forth their demands.…”
Section: Manuscript Received 7 August 2022; Accepted 19 May 2023mentioning
confidence: 66%
See 1 more Smart Citation
“…Countries with wealthier and more organised elites were, on average, slower in imposing lockdown measures. This resonates with recent studies focusing on policymaking during the pandemic in Europe, which has shown that pandemic politics became the focus of intense lobbying competition, in which business groups tended to predominate (Eady and Rasmussen, 2022). As Crepaz et al, (2022) argue, because the pandemic would cause important economic disruptions, governments had reason to prioritise the mitigation of financial distress on economic groups, particularly of those with the resources to put forth their demands.…”
Section: Manuscript Received 7 August 2022; Accepted 19 May 2023mentioning
confidence: 66%
“…The COVID emergency impacted the political arena by blocking some of the usual channels of influence (Edgell et al, 2020). 3 Most policy decisions were approved through emergency mechanisms and executive orders, which meant that many of the prevalent channels in “politics as usual,” like lobbying, were weakened or not available.…”
Section: Access To Policymakers In Times Of Crisis: Personalised and ...mentioning
confidence: 99%
“…At the same time, despite the uniqueness of our case, several studies document that lobbying after the outbreak of Covid-19 shared remarkable similarities with lobbying in non-crisis circumstances (cf. Bonafont & Iborra, 2021; Eady & Rasmussen, 2021; Junk et al, 2021). As Fraussen et al (2020) argue, the tendencies in lobbying in relation to the Covid-19 pandemic ‘also characterize policymaking in normal times’ and are therefore likely to have implications for lobbying beyond the Covid-19 case.…”
Section: Timing and Lobbying Influencementioning
confidence: 99%
“…A disadvantage related to this choice is, obviously, that we cannot generalize our empirical findings to a vast variety of cases, considering we have selected a salient issue with a large scope – and an unprecedented crisis . At the same time, however, despite the crisis circumstances and emergency policy-making powers in place in many countries, recent scholarship indicates that patterns of interest groups’ political activities are broadly comparable and surprisingly similar (with, of course, some differences) to non-crisis situations (Bonafont & Iborra, 2021; Eady & Rasmussen, 2021; Fraussen et al, 2020; Junk et al, 2021). This preliminary evidence can be seen as encouraging for the generalizability of our study, as it suggests that, while exceptional, the pandemic has not radically changed positions (Bonafont & Iborra, 2021), biases (Eady & Rasmussen, 2021) and access (Junk et al, 2021) in lobbying.…”
Section: A Theory Of Timing In Lobbying (Ii): Conditional Effectsmentioning
confidence: 99%
See 1 more Smart Citation